Pengaruh Sikap Kerja Kecerdasan Emosional Dan Budaya Kerja Terhadap Efektivitas Kerja Pegawai Badan Pendapatan Daerah Kabupaten Lahat - Wulandari, Wulandari; Hardiyansyah, Hardiyansyah; Oktala , Rosananda (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
The author conducted the research with the aim of knowing and analyzing the influence of work attitudes, emotional intelligence, and work culture individually and together on the work effectiveness of Lahat Regency Regional Revenue Agency employees. The research method used in this research is a quantitative method using questionnaires distributed to respondents. The analysis used is a descriptive and inferential analysis using statistical calculations with multiple regression formulas, partial tests, simultaneous tests, and coefficient of determination. The research results showed that work attitude, emotional intelligence, and work culture had a significant influence, individually and collectively, on the work effectiveness of Lahat Regency Regional Revenue Agency employees.